62 Tetranectin expression is associated with myocardial fibrosis and may be a useful serum biomarker for indicating early myocardial injury and predisposition to heart failure development. (16th October 2019) - Edgar, K; Glezeva, N; Collier, P; Ledwidge, M; O'Reilly, J; Tea, I; Baugh, J; McDonald, K; O' Connell, E; Watson, C
Abstract : Introduction: Heart failure (HF) is a major public health concern which requires improvements in effective diagnosis, management and treatment strategies. A previous proteomics biomarker discovery study identified Tetranectin, a protein involved in tissue remodelling and with associations with a number of cancers, as a potentially useful biomarker in heart disease. The aim of this study was to validate tetranectin as a potential HF biomarker candidate and investigate association with myocardial fibrosis associated with heart failure. Methods: For serum Tetranectin measurements samples from HF (n=40) and no-HF controls (n=60) were analysed by ELISA. Atrial tissue samples from cardiac surgery patients (n=32) were collected for analysis of gene expression levels by qPCR and histological investigation of myocardial fibrosis and tetranectin localisation. Myocardial tissue expression of tetranectin was also investigated in control and HF groups by western blotting. In-vitro investigations were performed using ventricular human cardiac fibroblast cells (vHCF) to investigate how changes in fibroblast tetranectin expression influences fibrotic/inflammatory processes. Results: Circulating tetranectin levels are significantly reduced in HF patients (P<0.0001), compared with controls, and are associated with HF more closely than B-type natriuretic peptide (p=0.011). Serum tetranectin negatively correlated with circulating fibrosis markers, whereas cardiac tissue tetranectin correlates positively with pro-fibrotic gene expression within the myocardium. Collagen 1 (p=0.056) and 3 (p=0.036), MMP2 (p=0.055), MMP9 (p=0.005), and TIMP1 (p=0.019) were all significantly correlated to myocardial tetranectin level and significantly increased deposition of collagen was observed in cardiac tissue of patients with high tetranectin protein expression (p=0.011). Pro-fibrotic stimulation of vHCF cells in-vitro resulted in altered tetranectin expression. Conclusions: We identified tetranectin as a promising novel HF biomarker that may be useful for the diagnosis or disease monitoring of patients at risk for HF or those with established HF. The data shows for the first time that there is significant tetranectin expression within human myocardium and found correlations with the degree of tissue fibrosis in HF. Due to its role in extracellular matrix remodelling this study indicates that the association of tetranectin with pro-fibrotic factors in the myocardium may be a useful tool in investigating the pathogenesis of HF. Taken together these data show that tetranectin may be promising as a HF biomarker, however further research is required to elucidate the mechanism for its role in the pathophysiology of cardiac fibrosis and HF.